Pengaruh Asupan Makanan terhadap Kejadian Malnutrisi di Rumah Sakit - Defriani Dwiyanti; Hamam Hadi; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2004)
Background: Sufficient food and other nutrient intake are necessary for recovery of hospitalized patients. Insufficient food intake may decrease nutrient metabolism, which in turn may cause malnutrition. Malnutrition in all hospital is categorized as high (about 40-45%). However, the influence of food intake on hospital malnutrition in Indonesia is still unknown.Objective: To assess the influence of nutrient intake on the occurence of hospital malnutrition.Method: This was an observational with prospective cohort study. This study as conducted in Dr. M. Jamil Padang Hospital, Dr. Sardjito Yogyakarta Hospital, and Sanglah Denpasar Hospital. Subjects were 228 adult patients from internal and neurology units in 1st, 2nd, and 3rd class who were hospitalized for six days or more, receiving oral diet, compos mentis, cooperative, non edema, and non ascites. Data of body weight and body height were measured at admission and discharge. Food intake data collected in this study included hospital and non-hospital food. Data analyzed by FP2 programme and STATA software.Results: Among 228 subjects of study, 51,8% had insufficient intake in the first three days of hospitalization. On average, their protein and energy intakes were lower than subjects with sufficient intake. There was a significant correlation between the first three days intake and intake during hospitalization (p<0,05). Subjects with insufficient energy intake were 2,1 times more likely to be malnourished in hospital than subjects with sufficient energy intake. Meanwhile, subjects with insufficient protein intake were 1,56 times more likely to be malnourished than subjects with sufficient protein intake. There was a significant association between energy intake and hospital malnutrition (p<0,05).Conclusions: Patients with insufficient nutrient intakes are more likely to be malnourished than those with sufficient nutrient intakes.